Analysis and optimization of sandwich tubes energy absorbers under lateral loading. (August 2015) - Baroutaji, A.; Gilchrist, M.D.; Smyth, D.; Olabi, A.G.
Abstract: In this paper, the sandwich tubes, which consist of thin-walled circular tubes with aluminium foam core, were proposed as energy absorption devices. The sandwich tubes were laterally crushed under quasi-static loading conditions. Detailed finite element model, validated against existing experimental results, was developed using the explicit code (ANSYS-LSDYNA) to assess the energy absorption responses and deformation modes. Response surface methodology (RSM) was employed in parallel with the finite element models to perform both parametric studies and multi-objective optimization in order to establish the optimal configuration of the sandwich tube. Sampling designs of the sandwich tubes were constructed based on a D – optimal design of experiment (DOE) method. Factorial analysis was performed using the DOE results to investigate the influences of the geometric parameters on the responses of sandwich tubes. In addition, multi-objective optimization design (MOD) of the sandwich tubes is carried out by adopting a desirability approach. It was found that the tube with a minimum diameter of the inner layer and a maximum foam thickness are more suitable for use as energy absorbing components. Highlights: The energy absorption characteristics of sandwich tubes are investigated under lateral loading. The crush behaviour of sandwich tube is evaluated via 3D finite element modelling and response surface method. The optimal design of the sandwich tubes was obtained via Desirability approach. The optimal design was found to have a minimum diameter of the inner layer and a maximum foam thickness.